Mitophagy in Cell Death Regulation: Insights into Mechanisms and Disease Implications - Jiani Lin; Xinyao Chen; Yuyang Du; Jiapeng Li; Tingting Guo; Sai Luo (Biomolecules)
Mitophagy, a selective form of autophagy, plays a crucial role in maintaining optimal mitochondrial populations, normal function, and intracellular homeostasis by monitoring and removing damaged or excess mitochondria. Furthermore, mitophagy promotes mitochondrial degradation via the lysosomal pathway, and not only eliminates damaged mitochondria but also regulates programmed cell death-associated genes, thus preventing cell death. The interaction between mitophagy and various forms of cell death has recently gained increasing attention in relation to the pathogenesis of clinical diseases, such as cancers and osteoarthritis, neurodegenerative, cardiovascular, and renal diseases. However, despite the abundant literature on this subject, there is a lack of understanding regarding the interaction between mitophagy and cell death. In this review, we discuss the main pathways of mitophagy, those related to cell death mechanisms (including apoptosis, ferroptosis, and pyroptosis), and the relationship between mitophagy and cell death uncovered in recent years. Our study offers potential directions for therapeutic intervention and disease diagnosis, and contributes to understanding the molecular mechanism of mitophagy.